Understanding Creolization Through Contextualization and Decontextualization Of Objects Found on Reunion Island (Journal of Advanced Research in Social Sciences, 2019)
This ethnographic study is looking at objects to understand the Creolization process on Reunion Island. Objects evoke memory, emotion, imagination and validation. On Reunion Island, objects from the past, such as during the period of slavery and marronage, have very often disappeared or left little trace of their existence. This void has sometimes been interpreted as a part of a ‘veil of silence’ on the island around this painful part of history. However, there are some objects, which were intended for use in one context that have been (and are still being) decontextualized and put to use in totally new contexts. At the same time, this process of contextualization and decontextualization can be applied to the creation of a recently discovered Kingdom of Marons, which existed in the centre of the island for over 200 years. Where the original names in old Malgasy, which many of the slaves spoke, were turned into similar sounding French words. This decontextualized the meaning and the original context. We can also apply the same decontextualization process to objects such as the Alambic, originally used for distilling rum and later for essential oils. Sabres used as sacred objects in ceremonies on Reunion Island, began their life as recycled suspension metal from old trucks used to transport sugar cane. An examination of these practices and the role contextualization and decontextualization plays is a means to understand the process of Creolization on Reunion.